Highly sensitive enhanced chemiluminescence immunodetection method for herpes simplex virus type 2 Western immunoblot. - Dalessio, J (1992)
Three Western blot (immunoblot) methods for detecting antibodies to herpes simplex virus type 2 were compared: (i) nitrocellulose blots with 4-chloro-1-naphthol immunostaining (4CN-WB); (ii) polyvinylidene difluoride (PVDF) blots with 3,3',5,5'-tetramethylbenzidene immunostaining (TMB-WB); and (iii) PVDF blots with enhanced chemiluminescence (ECL-WB). TMB-WB was 10-fold more sensitive than 4CN-WB, while ECL-WB was as much as 500-fold more sensitive.